Information technologies in healthcare: features of sectoral implementing - S. U. Soboleva; V. V. Golikov; A. A. Tazhibov (E-Management, 2021)
The article investigates the features of the industrial application of information technologies in healthcare. Information technologies have become not only an integral part of economic and social life, but also in some sectors the leading basis for the implementation of activities. At the same time, there are both basic formats of their application that do not depend on a specific sphere, and specific ones that are characteristic of each specific industry. The ratio of ordinary and unique programs varies depending on the application area. Healthcare is characterized by a large number of unique technological products that directly help in the treatment of patients, and at the same time, there is a shortage of basic, including managerial digital technologies, which are either completely absent or are implemented to a small extent.Currently, several digital projects are in the process of development and implementation, aimed at optimizing interaction not only at the doctor–doctor level, but also at the doctor–patient level. The main tasks of these projects, in addition to automating an appointment with a doctor, medical examination, preferential medicines, regardless of the region where the patient is located, are to achieve solutions to issues related to the problems of early diagnosis of diseases remotely and in a short time. The need for this was clearly demonstrated by the coronavirus pandemic.